Community perception of the rural landscape heritage conservation / Siti Marlamah Mazehan - Mazehan, Siti Marlamah (2014)
Rural landscape was evolved or developed through the interaction of human-environment relationship from a long time ago and was created a landscape that has its own identity. Thus, conserving the rural landscape heritages is significant to ensure that it not been taken up by rapid development, climate change and also other threats. The study on rural landscape heritage conservation is still new in Malaysia. There is much information needed in order to preserve and conserve rural landscape heritage in Malaysia. One of the issues is on community perception on the rural landscape heritage conservation. This research is aimed to evaluate the community perception on the rural landscape heritage conservation. Three objectives has been developed to achieve the goal of this research. First is to understand the community perception on the rural landscape heritage. Second is to investigate the views of the rural landscape from community perspectives. Third is to recommend fundamental ways in enhancing the rural landscape value in Malaysia. Methods used to gather the data are visual observation, questionnaires survey and focus group discussion. Study area were consisted of a rural landscape area in Lenggong, Perak. Observation includes taking a photograph of rural landscape of Lenggong as guided by a set of criteria. Selected photographs used in the questionnaires. It consisted of demographic profile, Likert-scale questions and open ended questions. Focus group discussion conducted to support data needed. The data were analyzed by using SPSS and manual transcription. Then it was triangulated between questionnaire survey and focus group discussion. The outcome is the understanding of community on rural landscape heritage. It included community perception on the rural heritage, problem in maintaining rural heritage and role of community in managing the rural heritage. Besides that, community in Lenggong has view the rural landscape character of Lenggong based on their perception. It included which landscape should be preserve and conserve, threatened and give benefit to the community. At the last phase, researcher has provided the recommendation in enhancing the value of rural landscape.